A REVIEW OF STUDENTS' INTEREST IN THE SPORT OF SHORT DISTANCE RUNNING (SPRINT) IN CLASS V OF SD TUNAS HARAPAN TANJUNG ANOM: TINJAUAN TENTANG MINAT SISWA TERHADAP CABANG OLAHRAGA LARI JARAK PENDEK (SPRINT) PADA KELAS V SD TUNAS HARAPAN TANJUNG ANOM - Fauzan, Fandy (UPMI Proceeding Series, 2024)
Short distance running (sprint) is one of the game sports taught in elementary schools (SD) contained in the physical education curriculum where students need to improve skills and techniques in its implementation. The purpose of this study was to determine students' interest in short distance running (sprint) in class V SD Tunas Harapan Tanjung Anom TA 2023/2024. This research was conducted using a qualitative approach. The nature of the research is descriptive and this type of research is classroom action research with observation and interviews. The approach used a qualitative approach to the four stages that are passed in carrying out classroom action research, namely planning, acting, observing and reflecting. In addition, a research design consisting of an initial test was also used, observation and reflection and cycle. Students' interest in short distance running (sprint) in Class V SD Tunas Harapan Tanjung Anom is still low due to the lack of student interest and ability to do short distance running (sprint) 50 because the teaching method used is too monotonous, so that it does not provide a variety of play in providing teaching material and is less targeted in providing explanations and examples of the implementation of the real 50 metre short distance running (sprint). For this reason, it is recommended that physical education teachers need to be creative in designing teaching methods and processes that are modified in the form of games to attract student interest and focus.